Beauty in Efficiency: An Experimental Enquiry Into the Principle of Maximum Effect for Minimum Means. (January 2017) - da Silva, Odette; Crilly, Nathan; Hekkert, Paul
Theory and discourse suggest that the aesthetic appreciation of a wide range of artifacts—including works of art and consumer products—is partially governed by the principle of maximum effect for minimum means. We conducted two studies to find experimental evidence of this principle in the context of product design. In Study 1, we tested the hypothesis that the aesthetic appreciation of a product would be positively affected by the perception of the product as the minimum means achieving the maximum effect. Encouraged by the results of this study, we conducted Study 2 to test again the principle of maximum effect for minimum means using a more controlled experimental design. Our findings provide support for our hypothesis, indicating that the aesthetic appreciation of a product depends, to some extent, on the perception that the product achieves more than other products from its category by making an efficient use of resources.